2017
DOI: 10.5607/en.2017.26.6.390
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Separation Does Not Produce a Significant Behavioral Change in Mice

Abstract: Early life adversities together with genetic predispositions have been associated with elevated risks of neuropsychiatric disorders during later life. In order to investigate the underlying mechanisms, many chronic, early-life stress paradigms in multiple animal models have been developed. Previously, studies reported that maternal separation (MS) in the early postnatal stages triggers depression-and/or anxiety-like behaviors in rats. However, similar studies using mice have reported inconsistent behavioral ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 38 publications
3
27
0
Order By: Relevance
“…Increased anxiety-like behavior and activity levels were also seen in MSEW adult male mice of a recent study (Murthy et al, 2019). However, postnatal maternal separation (MS) demonstrated no clear and consistent effects on behavioral phenotypes in a variety of strains of mice in the other studies (Millstein and Holmes, 2007;Tan et al, 2017). Taken together, the results of present study and previous ones demonstrate that the MSEW mice and rats can be used as a robust model to mimic early life neglect and abuse in humans.…”
Section: Msew Inhibits Ols Maturation and Myelination In Pfc Of Rats:supporting
confidence: 41%
“…Increased anxiety-like behavior and activity levels were also seen in MSEW adult male mice of a recent study (Murthy et al, 2019). However, postnatal maternal separation (MS) demonstrated no clear and consistent effects on behavioral phenotypes in a variety of strains of mice in the other studies (Millstein and Holmes, 2007;Tan et al, 2017). Taken together, the results of present study and previous ones demonstrate that the MSEW mice and rats can be used as a robust model to mimic early life neglect and abuse in humans.…”
Section: Msew Inhibits Ols Maturation and Myelination In Pfc Of Rats:supporting
confidence: 41%
“…In one study, eight different strains of mice were used to examine the effect of MS in adults, and it was found the typic protocol of MS that pups were separated from their dams for 3 hr per day from P0-P13 did not significantly affect the anxiety and depressive level in all strains (Millstein & Holmes, 2007). Another work studied two protocols of MS, one separating pups from their dams from P2 to P14, 3 hr per day, and another using the same protocol of MS but with increasing hours of separation plus an early weaning at P17, showed that both protocols had no significant effect on anxiety-related and depression-like behaviors in adults (Tan, Ho, Song, Low, & Je, 2017). These results are in contrast with many other studies using a variety of MS protocols in mice showing the effect of MS on anxiety-related and depression-like behaviors in adulthood (Lesse, Rether, Gröger, Braun, & Bock, 2017;Romeo et al, 2003;Tchenio et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Both of these approaches mimic the “dose-response” or “cumulative” stress links to mental illness that have been described in humans. However, like the other rodent models of ELS, data from these two-hit models need to be interpreted with caution as null effects have also been reported (Santarelli et al, 2017 ; Tan et al, 2017 ).…”
mentioning
confidence: 99%